Ethnicity and conflict severity: accounting for the effect of co-ethnic and non-ethnic militias on battlefield lethality. Issue 3 (4th March 2019) - Aliyev, Huseyn; Souleimanov, Emil A.
Abstract: How does the presence of armed pro-regime groups affect conflict lethality? This study examines the relationship between ethnicity, militia violence and conflict lethality in civil wars. We emphasise that differences in whether pro-regime militias were recruited in accordance with their ethnicity or not are critical in their influence upon conflict lethality, which we estimate in battlefield deaths. To that end, we categorise militias into groups recruited on their ethnic basis (co-ethnic militias) and those recruited regardless of their ethnicity (non-ethnic militias). We hypothesise that conflicts are more lethal when non-ethnic militias are involved. We link higher number of battle-deaths in conflicts with non-ethnic militias with the militia use of one-sided violence against civilians. Co-ethnic militias – that is militias recruited from the same ethnicity as rebels – are deployed amongst their co-ethnics and therefore tend to target civilians less than non-ethnic militias. This militia–civilian relationship has direct impact on conflict severity. To test our hypotheses we conduct global statistical analysis of 84 intrastate conflicts from 1989 to 2014.